2014
DOI: 10.5897/ijgmb2013.0089
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning and distribution of random amplified polymorphic DNA (RAPD) variation among eggplant Solanum L. in Southwest Nigeria

Abstract: Solanum L., the largest genus of the Solanaceae family, vary morphologically, is diverse in number and is ecogeographically distributed. In Nigeria, previous studies had focused mainly on chromosome morphology, genome description and medicinal values, which are insufficient for genetic affinities. This study used four highly polymorphic random amplified polymorphic DNA primers to describe both the genetic relatedness and variability among 25 accessions of eggplant from Southwestern Nigeria. At a truncated line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
(30 reference statements)
2
6
1
Order By: Relevance
“…On this note, the phylogenetic tree has revealed that the cultivars are separated into eight different species, though some are closely related along a common ancestral lineage while some appeared to be primitive progenitors showing a divergent relationship. This finding therefore agrees with reports of convergent and divergent relationships on eggplant accessions using molecular marker approach (Sifau et al, 2014;Aguoru et al, 2015b).…”
Section: Resultssupporting
confidence: 93%
“…On this note, the phylogenetic tree has revealed that the cultivars are separated into eight different species, though some are closely related along a common ancestral lineage while some appeared to be primitive progenitors showing a divergent relationship. This finding therefore agrees with reports of convergent and divergent relationships on eggplant accessions using molecular marker approach (Sifau et al, 2014;Aguoru et al, 2015b).…”
Section: Resultssupporting
confidence: 93%
“…For each PCR reaction mixture, one (1) washed FTA disc (contained the DNA template), 18µl of molecular water and 1µl of one specific primer pair were mixed in a PCR tube already containing a customized BIONEER ® Accupower PCR Premix to make a total of 20µl as the reaction volume. The PCR tubes were loaded on the thermal cycler and programmed with the appropriate temperature profile following the method of Sifau et al (2014). The amplified DNA sample in each tube was dispensed into an agarose gel pore inside an electrophoresis tank connected to Consort EV243 electrophoresis power supply.…”
Section: Methodsmentioning
confidence: 99%
“…This species is further grouped into different ecotypes which are; Aculeatum, Gilo, Kumba and Shum group as revealed by similarities in genotypic characterization though varied phenotypes exist (Sharmin et al, 2011). However, some authors have argued that the four groups in S.aethiopicum be treated as different species since they all display varied phenotypes and genotypes using a combination of molecular markers (Nunome et al, 2001;Sifau et al, 2014 ). Apart from the four species stated above, taxonomists have also identified and reported other Solanum species including S. incanum, S. scabrum, S. dasyphyllum and S. erianthum (Agnieszka et al, 2007;Osei et al, 2010;Knapp et al, 2013;Mariola et al, 2014;Sifau et al, 2014) while many species are yet to be identified, named and classified systematically (Agnieszka et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations